Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376795
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal and Mixed Control of Robotic Endoscopes

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 66 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…In our experiments, this human camera assistant is replaced by the Virtuose6D 5 ( Haption SA , Laval, France) robotic arm. As shown in ( Avellino et al, 2020 ), the dimensions, workspace, and supported payload of this robotic arm are well suited for robotic endoscope control 6 . The operational workspace is defined as a cube of side 450 mm and is located in the center of the workspace envelope.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our experiments, this human camera assistant is replaced by the Virtuose6D 5 ( Haption SA , Laval, France) robotic arm. As shown in ( Avellino et al, 2020 ), the dimensions, workspace, and supported payload of this robotic arm are well suited for robotic endoscope control 6 . The operational workspace is defined as a cube of side 450 mm and is located in the center of the workspace envelope.…”
Section: Methodsmentioning
confidence: 99%
“…In their experimental setup, the system could track either a single instrument or the midpoint between two tools. Similarly, Avellino et al (2020) have also employed kinematics for autonomous endoscope guidance in a co-manipulation scenario 1 . In ( Casals et al, 1996 ; Mudunuri, 2010 ), rule-based strategies switch the control mode between single-instrument tracking or tracking points that aggregate locations of all visible instruments.…”
Section: Related Workmentioning
confidence: 99%
“…Video capture (Figure 6b) is "more suitable for some steps of the projects" -p43, "all of our actions would be recorded" -p6. Interestingly, 11 of the 12 respondents who considered Capush for the activity "electronic" 6 would record videos with Capush, which 6 The survey software selected the two activities for which participants indicated capturing most frequently pictures or videos. Questions on current practices were asked for both activities, whereas exploration of Capush was centered on the Proc.…”
Section: Rq2: Exploration Of Framework Dimensions Through Capushmentioning
confidence: 99%
“…Both manual and automatic control require some form of user interface though to indicate where the camera should point or tell an automated control what to keep in the field of view. Depending on the level of indirection [8] and the desired automation, different control interfaces are possible, much of which have already been explored in previous work for both manual [25] and mixed control [6]. With our proof-of-concept prototype, we tested a basic implementation of the automatic tracking mode mentioned in the study and the video shown to respondents.…”
Section: Proof Of Concept Implementationsmentioning
confidence: 99%
“…Regarding the interaction technique to capture information during surgery, HCI research has explored voice and gesture-based systems [45,52] that are compatible with the sterility requirements. Touch can also be used for instance by using a sterile cover around buttons on the endoscope, although oftentimes surgeons are busy holding the surgical tools and cannot simply switch to the endoscope to press buttons [4].…”
Section: Implication: Making Video a Communicative Artifactmentioning
confidence: 99%